Drop Height and Volume Control the Mobility of Long‐Runout Landslides on the Earth and Mars. Issue 24 (23rd December 2017) - Johnson, Brandon C.; Campbell, Charles S.
Abstract: Long‐runout landslides are landslides with volumes of 10 5 m 3 or more, which move much farther from their source than expected. The observation that Martian landslides are generally less mobile than terrestrial landslides offers important evidence regarding the mechanism responsible for the high mobility of long‐runout landslides. Here we simulate landslides as granular flow using a soft‐particle discrete element model. We show that while surface gravity plays a negligible role, observed differences in fall height naturally reproduce the observed differences in mobility of Martian and terrestrial landslides. We also demonstrate that landslides on Iapetus may fit this trend. Our simulations do not include any fluid and indicate that a mechanism similar to acoustic fluidization can explain the high mobility of long‐runout landslides. This implies that long‐runout landslides on Mars should not be considered as evidence for ice, saturated clays, or liquid water. Key Points: We explore the striking difference between the mobility of long‐runout landslides on the Earth and Mars We simulate long‐runout landslides as granular flow using a soft‐particle code Differences in drop height explain the difference in volume mobility trends of Martian and terrestrial landslides